(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The study objectives were to develop multicomponent formaldehyde-killed and alum-adjuvanted Salmonella Enteritidis (SE) phage-type vaccines in chickens. Materials and Methods: SEPTs 35, 7, 6A, 3A, and 1 were killed, mixed to prepare six combinations, namely, V635, V671, V673, V675, and V613 and administered (0.20 ml) to chicks (n = 124) of 6 groups (CV635, CV671, CV673, CV675, and CV613), and one non-administered group as a control. Other chicks underwent 0.20 ml with SE 6A per chick (1,010 cfu per ml) as a challenge and were labeled CVZC, CV635C, CV671C, CV673C, CV675C, and CV613C. The blood, swab of cloaca, liver, spleen, digesta of the middle part of the intestine, and digesta of the cecum samples were collected for Salmonella detection. The caecum, bursa of Fabricius, liver, spleen, and ileum tissues were collected for histopathological examination. Results: Salmonella was detected (100%) from the digesta of the middle part of the intestine, swabs of the cloaca, digesta of the caecum, and blood, spleen, and liver samples in the CVZC. Salmonella was not detected from the 3 (50%), 2 (33%), and 1 (17%) samples in the CV671C and CV673C, CV613C and CV635C, and CV675C, respectively. Histopathological changes were mild (lesion scoring of 0.4/3.0) and recorded in the group CVZC in the ileum, cecum, and bursa of Fabricius on days 7 and 14 pc, respectively. Conclusions: All combinations of killed SEPTs could protect the chick against SE infection. However, V673 and V671 products are safer and more effective compared to other products. J. Adv. Vet. Anim. Res., 12(4): 1286–1296, December 2025 http://doi.org/10.5455/javar.2025.l989